Evaluation of the Papuan Special Autonomy Fund Policy: A Review of the Literature on Accountability, Targeting, and Justice for the Indigenous Papuans - Isak Klafle; Ulul Albab; Sapto Pramono; Dian Ferriswara (International Forum of Researchers and Lecturers, 2026)
The Papua Special Autonomy Fund (Dana Otonomi Khusus Papua) represents a key instrument of Indonesia’s asymmetric fiscal decentralization aimed at reducing historical inequalities, accelerating regional development, and promoting social justice for Indigenous Papuans. However, after more than two decades of implementation, concerns persist regarding its effectiveness in producing equitable welfare outcomes, particularly with respect to accountability, targeting accuracy, and distributive justice. This literature review critically examines existing scholarly research on the governance, implementation, and impacts of Dana Otsus Papua, with an emphasis on how institutional arrangements shape policy performance and equity outcomes. The study employs a narrative–critical literature review enriched with systematic elements, including transparent search procedures, explicit inclusion and exclusion criteria, and thematic synthesis. Peer-reviewed journal articles and reputable conference proceedings were analyzed using thematic analysis and conceptual mapping to identify dominant findings, methodological approaches, and research gaps. The synthesis reveals recurring patterns across the literature. Accountability mechanisms remain fragmented and weakly integrated across planning, budgeting, monitoring, and evaluation processes. Targeting accuracy is inconsistent, with fiscal benefits frequently failing to reach Indigenous Papuans as intended. Moreover, distributive justice outcomes depend more on institutional recognition, participation, and governance capacity than on the size of fiscal transfers alone. The review also highlights a critical gap in integrative evaluations that link governance arrangements, implementation processes, and equity outcomes. The article concludes that improving Dana Otsus Papua requires a shift from expenditure-focused assessments toward governance- and justice-oriented evaluation frameworks. The study contributes theoretically by integrating accountability, implementation, and distributive justice perspectives, and offers practical insights for strengthening oversight, refining targeting mechanisms, enhancing participatory governance, and embedding digital tools within accountability systems.